Ectopic Thyroid Tissue in Submandibular Region in Pediatric Patient: A Case Report - Bajracharya, Rohita; Dutta, Heempali (Journal of Institute of Medicine Nepal, 2020)
Normal anatomical location of thyroid gland is anterior to trachea and larynx. Ectopic thyroid is rare presentation. Ectopic thyroid tissue in submandibular region is even more rare. This article reports a case of five year old child who presented with swelling in left submandibular region which was later diagnosed to be an ectopic thyroid gland with no thyroid tissue in thyroid bed. Although rare, physician should consider possibility of ectopic thyroid in patient presenting with submandibular mass. Ultrasonography should always be performed to confirm presence of normal thyroid gland if surgical excision is planned.